Fully biobased thermoplastic elastomers: Synthesis of highly branched linear comb poly(β-myrcene)-graft-poly(l-lactide) copolymers with tunable mechanical properties. (28th February 2018) - Zhou, Cheng; Wei, Zhiyong; Jin, Chenhao; Wang, Yanshai; Yu, Yang; Leng, Xuefei; Li, Yang
Abstract: Biobased thermoplastic elastomers are of interest for their merits, especially renewability and sustainability. In this work, a series of fully biobased linear comb poly(β-myrcene)- graft -poly(l -lactide) (PM- g -PLLA) copolymers consisting of interior rubbery block and exterior semicrystalline block were synthesized via ring-opening polymerization ofl -lactide using hydroxylated poly(β-myrcene) as macroinitiator. To evaluate the effects of branch length and graft density of poly(β-myrcene) on the performances of these obtained copolymers, the chemical compositions and molecular weights, crystal structures and spherulite morphologies, phase morphologies, thermal and mechanical properties were systematically analyzed by various techniques. Analysis of NMR and GPC indicated that graft copolymers were successfully obtained as designed. Two distinct glass transitions corresponding to the two building blocks observed from both DMA and DSC measurements suggested the occurrence of microphase separation, which was further confirmed by SAXS and AFM morphological characterizations. Results of DSC, WAXD, and POM showed that the crystallization behavior of the graft copolymers depends on graft density and branch length. Tensile test suggested that the mechanical properties of graft copolymers depend on PM/PLLA composition, particularly graft density and branch length, which could be readily tailorable to different applications. Graphical abstract: Highlights: Biobased poly(β-myrcene) was used as the rubbery block for polylactide based TPEs. The structure-property relationships of poly(β-myrcene)-graft-poly(l -lactide) copolymers were investigated. The mechanical properties of graft copolymers depend on composition and complex architecture.